Idea and Image in Recent Art. - The Art Institute of Chicago (Chicago : The Art Institute of Chicago, 1974)
Acconci, Vito ; Anselmo, Giovanni ; Baldessari, John ; Becher, Hilla & Bernd ; Beuys, Joseph ; Bochner, Mel ; Boltanski, Christian ; Cage, John ; Craig-Martin, Michael ; Darboven, Hanne ; Dine, Jim ; Huebler, Douglas ; Johns, Jasper ; Kienholz, Edward ; Kosuth, Joseph ; Lichtenstein, Roy ; Morris, Robert ; Nauman, Bruce ; Rauschenberg, Robert ; Warhol, Andy ; Wegman, William ; Weiner, Lawrence ; Wiley, William
Idea and Image in Recent Art, The Art Institute of Chicago, March 23 - May 5, 1974
boek